Advanced Computational Methods and Experiments in Heat Transfer XI 2010
DOI: 10.2495/ht100221
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of heat transfer in the finite element process modelling of inertia friction welding of SCMV and AerMet 100

Abstract: Inertia friction welding is the process in which stored kinetic energy in a flywheel is converted to heat by relative sliding movement between the components' surfaces. The process is widely used in joining high strength aero-engine alloys. Heat transfer interactions play a fundamental role in determining weld quality as temperature has a significant impact on the mechanical, thermal and metallurgical behaviours of materials. Heating and cooling rates influence thermal stresses induced by variations in materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Material Forming ESAFORM 2014 (coulomb friction) was specified at the interface between the components as a function of process time as specified by Bennett et al [8]. The value for the interface heat transfer coefficient was specified as 1×10 4 N/s/mm/K following the study of Mohammed et al [16] . The initial rotation velocity of 122.5 rad/s was defined using energy based method giving the die an initial energy of 2.3286×10 8 Nmm with a moment of inertia 30973 Nmms 2 .…”
mentioning
confidence: 99%
“…Material Forming ESAFORM 2014 (coulomb friction) was specified at the interface between the components as a function of process time as specified by Bennett et al [8]. The value for the interface heat transfer coefficient was specified as 1×10 4 N/s/mm/K following the study of Mohammed et al [16] . The initial rotation velocity of 122.5 rad/s was defined using energy based method giving the die an initial energy of 2.3286×10 8 Nmm with a moment of inertia 30973 Nmms 2 .…”
mentioning
confidence: 99%
“…During the initial heating stage, the authors showed that frictional shear stress depends on the interaction of surface asperities and is affected by the axial pressure and flow stress of the material. Mohammed et al (2010) performed a simulation of IFW of SCMV to AerMet-100 with the aim of investigating the importance of heat transfer modes during the process.…”
Section: Numerical Modelling Of Metalsmentioning
confidence: 99%
“…Yang, 2010). Mohammed et al (2010) concluded that conduction dominates the other heat transfer mechanisms during the welding stage, and that considering convection and radiation has little influence because the temperature gradient in the pipes surpasses that between the pipes and the environment. Conduction also remains the controlling heat transfer mode during the primary stage of cooling.…”
Section: Boundary Conditionsmentioning
confidence: 99%